Farmers embrace Striga control in Nigeria - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Farmers in over 50 communities in Nigeria s Middle Belt, often known as the food basket of the country, have successfully used Striga control methods to increase crop productivity and improve their livelihoods.